STRATEGI KOMUNIKASI PEMASARAN TERPADU NATURE CAKES DALAM MEMBANGUN BRAND AWARENESS HEALTHY CAKES - Purwita, Gst Ayu Mika Indah; Pascarani, Ni Nyoman Dewi; Suryawati, I Gusti Agung Alit (E-Jurnal Medium, 2019)
ABSTRACT Nature Cakes is a MSME engaged in the business of Food, especially Cakes. Nature Cakes innovates by developing new cakes, so that new cakes are created besides tasty, also healthy for the body, in accordance with the jargon carried by